The conception of humanism and its significance for nursing and the profession of a nurse - Kowalik, Grażyna (Medical Studies/Studia Medyczne, 2016)
In a few last decades there has been a change in the way the role of nursing is regarded. Education of nurses is now a part of university courses, which undoubtedly means higher expectations concerning this profession. Enabling professional nurses to perform their duties well requires more than just expertise, skills, and competences; what is necessary is deep emotional engagement with their work, which is reflected by their adequate, highly humanistic response to the individual needs of a particular patient. Many theoreticians of nursing point out in their models and theories the importance of humanistic aspects in terms of professional activities performed by nurses. The aim of this paper is to attempt to review the existing theories concerning nursing, focusing on the values of humanism, and to emphasise their significance for nursing practice.